1993
DOI: 10.1259/0007-1285-66-784-375
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy—an effective treatment for vaginal verrucous carcinoma

Abstract: Vaginal carcinoma makes up 1%-2% of all gynaecological tumours. Verrucous carcinoma of the vagina is even more rare--only 16 cases are reported in the scientific literature. A case of a complete regression after 60 Gy fractionated radiotherapy by a tumour 12 cm3 in size is reported. Most authors are of the opinion that radiotherapy causes anaplastic transformation of verrucous carcinoma. The minority view, that anaplastic transformation does not occur, is correct and is supported by our clinical and radiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Different modalities have been proposed for treatment, such as surgery, cryosurgery, radiation therapy, 48,49 α‐interferon, 50,51 systemic retinoids, 52 and also chemotherapies using methotrexate, 53 bleomycin, 54 or 5‐fluoruracil 55 . Controversy persists concerning irradiation for managing verrucous carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different modalities have been proposed for treatment, such as surgery, cryosurgery, radiation therapy, 48,49 α‐interferon, 50,51 systemic retinoids, 52 and also chemotherapies using methotrexate, 53 bleomycin, 54 or 5‐fluoruracil 55 . Controversy persists concerning irradiation for managing verrucous carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy persists concerning irradiation for managing verrucous carcinoma. Despite reports describing the radiation‐associated anaplastic transformation of the tumor, 22,56 radiation therapy is frequently used in patients with extensive comorbidity precluding surgery 47–49 . Koch and coworkers 47 recently analyzed 2350 cases of verrucous carcinomas and showed that patients with initial surgical treatment had a longer survival than those treated with irradiation (88.9 vs. 57.6%).…”
Section: Discussionmentioning
confidence: 99%
“…genitalen Schleimhaut (vaginal,perianal, zervikal) sind seltener als verruköse Karzinome des Penis [4,22].Als Rarität wurden auch verruköse Karzinome der Blasenschleimhaut im Zusammenhang mit Schistosomiasis beschrieben [11].…”
Section: Besprechungunclassified